Barriers to clinical adoption of next-generation sequencing: a policy Delphi panel's solutions. (July 2017) - Messner, Donna A; Koay, Pei; Naber, Jennifer Al; Cook-Deegan, Robert; Majumder, Mary; Javitt, Gail; Dvoskin, Rachel; Bollinger, Juli; Curnutte, Margaret; McGuire, Amy L
Aim: Identify solutions to the most important policy barriers to the clinical adoption of next-generation sequencing.Materials & methods: Four-round modified policy Delphi with a multistakeholder panel of 48 experts. The panel deliberated policy solutions to (previously reported) challenges deemed most important to address.Results: The group advocated using consensus panels to promote consistency in payer policies and to standardize test reporting, and favored making genomic data-sharing a condition of regulatory clearance, certification, or accreditation processes. They were split on the role of US FDA.Conclusion: Panelists found common ground on solutions for health plan coverage policy consistency, data-sharing, and standardizing reporting, but were sharply divided on the role of the FDA in mitigating risks to patients.